A prospective three‐step intervention study to prevent medication errors in drug handling in paediatric care. Issue 1 (3rd June 2014) - Niemann, Dorothee; Bertsche, Astrid; Meyrath, David; Koepf, Ellen D; Traiser, Carolin; Seebald, Katja; Schmitt, Claus P; Hoffmann, Georg F; Haefeli, Walter E; Bertsche, Thilo
<x xml:space="preserve">Abstract</x> Aims and objectives To prevent medication errors in drug handling in a paediatric ward. Background One in five preventable adverse drug events in hospitalised children is caused by medication errors. Errors in drug prescription have been studied frequently, but data regarding drug handling, including drug preparation and administration, are scarce. Design A three‐step intervention study including monitoring procedure was used to detect and prevent medication errors in drug handling. Methods After approval by the ethics committee, pharmacists monitored drug handling by nurses on an 18‐bed paediatric ward in a university hospital prior to and following each intervention step. They also conducted a questionnaire survey aimed at identifying knowledge deficits. Each intervention step targeted different causes of errors. The handout mainly addressed knowledge deficits, the training course addressed errors caused by rule violations and slips, and the reference book addressed knowledge‐, memory‐ and rule‐based errors. Results The number of patients who were subjected to at least one medication error in drug handling decreased from 38/43 (88%) to 25/51 (49%) following the third intervention, and the overall frequency of errors decreased from 527 errors in 581 processes (91%) to 116/441 (26%). The issue of the handout reduced medication errors caused by knowledge deficits regarding, for instance, the correct 'volume of solvent for IV drugs' from 49–25%. Conclusion Paediatric drug handling is prone to errors. A three‐step intervention effectively decreased the high frequency of medication errors by addressing the diversity of their causes. Relevance to clinical practice Worldwide, nurses are in charge of drug handling, which constitutes an error‐prone but often‐neglected step in drug therapy. Detection and prevention of errors in daily routine is necessary for a safe and effective drug therapy. Our three‐step intervention reduced errors and is suitable to be tested in other wards and settings.